Electric-Based Heating System for Cold Start and Idling Performances Enhancement of Carburetor Engine Fueled with Bio-Ethanol - Nguyen, Duy Tien; Nguyen, Duc Khanh; Nguyen, The Truc (JST: Engineering And Technology For Sustainable Development, 2024)
Bio-ethanol, one of the most popular alternative fuels, has been applied widely in the world to replace conventional fuel in internal combustion engines, especially in spark ignition engines. Bio-ethanol fuel is characterized by higher heat of vaporization value and low Reid vapor pressure in comparison with conventional gasoline fuel. These properties contribute to the lower temperature of the intake mixture and less effective mixture formation, which then affect engine performance, especially at cold starting and idling conditions. In this study, an electric-based heating system (EHS) was designed to increase intake air temperature, enhancing cold starting ability and idling stability. The experimental results show that, with the EHS, the cold start ability of the testing engine improves remarkably at low ambient temperature conditions. In addition, the cold idling speed of the test engine in the case of using EHS is more stable than the case of without the system.